Barriers to moving: Potential implications for the life satisfaction of young families - Guy Gellatly; Helen Foran; Lauren Pinault (Economic and Social Reports)
Rising housing costs have had an impact on the ability of families to move. This article, using data from the Canadian Social Survey (CSS), illustrates how higher prices have disproportionately affected the moving decisions of young Canadians, particularly those experiencing financial hardship.